Conhecimento do enfermeiro sobre as ações de vigilância epidemiológica no Hospital Universitário Onofre Lopes, Natal, RN - Ribeiro, Luciana Melo (2010)
This is an exploratory descriptive study with quantitative approach, aiming to verify the nurses' knowledge concerning the epidemiological surveillance activities at the Onofre Lopes hospital (HUOL), in Natal, Rio Grande do Norte. The study was performed with 63 nurses from the hospital and the data were collected through a questionnaire. All data were analyzed using descriptive statistics. The results were discussed and organized into four sections: nurses' knowledge on hospital epidemiological surveillance; procedures of the professional nurse through compulsory notification diseases; difficulties found by nurses to register the compulsory notification diseases and suggestions of strategies to joint epidemiological surveillance service with the care practices of nurses. The results showed that 55.55% of nurses know the main action of epidemiological surveillance, compulsory notification of diseases, and that 42.86% reported to the Hospital Epidemiology Center , while 57.14% did not allocate the information for this service. Most nurses found it difficult to perform notification for not knowing its flow; for the surveillance service does not operate 24 hours and for vagueness on diagnostic of disorders. Suggestions of strategies to improve the quality of epidemiological information are focused on training of nurses in hospital epidemiological surveillance; working in partnership with the surveillance center; diffusion of information on surveillance and conducting a daily active search. It comes to conclusion that most nurses don't notify the Surveillance Center about Compulsory Notification Diseases and it wasn't observed the incorporation of integrality values between the hospital surveillance and all nurses, since this principle guides the actions of health services based on dialogue, listening, ethical commitment, sharing of knowledge among professionals of various services and respect towards other professionals. Therefore, the integrality gap in the actions of the nurses studied, as well as in the surveillance service does not mobilize the potential of such services to changes in the sense of achievement of practices aimed at a special attention model that combines preventive and corrective actions, proposed and desired by SUS. Through the difficulties presented, it becomes important to recommend educational processes with strategy to transform the conducts, besides proposing actions under the principle of integrality provide responses agile and effective, as the purpose of VE hospital emergency care by the current epidemic